Предмет: Алгебра,
автор: maxlarcov74
уравнение 5 (2y - 3 ) +11 =6y
-2 ( 7-a) + 10 = a
-5 -3 ( 2b - 1 ) = 4b-22
Ответы
Автор ответа:
0
5( 2y - 3 ) + 11 = 6y
10y - 15 + 11 = 6y
4y = 4
y = 1
Ответ 1
-2 ( 7 - а ) + 10 = а
- 14 + 2а + 10 = а
- 4 = - a
а = 4
Ответ 4
- 5 - 3( 2b - 1 ) = 4b - 22
- 5 - 6b + 3 = 4b - 22
- 2 - 6b = 4b - 22
10b = 20
b = 2
Ответ 2
10y - 15 + 11 = 6y
4y = 4
y = 1
Ответ 1
-2 ( 7 - а ) + 10 = а
- 14 + 2а + 10 = а
- 4 = - a
а = 4
Ответ 4
- 5 - 3( 2b - 1 ) = 4b - 22
- 5 - 6b + 3 = 4b - 22
- 2 - 6b = 4b - 22
10b = 20
b = 2
Ответ 2
Похожие вопросы
Предмет: Физика,
автор: alinahudoarova89
Предмет: Французский язык,
автор: svetlanalvdvdvl
Предмет: Алгебра,
автор: va5ilievaalina704
Предмет: Алгебра,
автор: nasty1806
Предмет: Математика,
автор: sofiy12345com